2021
DOI: 10.1091/mbc.e20-09-0568
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching step analysis for robust determination of protein complex stoichiometries

Abstract: The counting of discrete photobleaching steps in fluorescence microscopy is ideally suited to study protein complex stoichiometry in situ. The counting range of photobleaching step analysis has significantly improved with more sophisticated algorithms for step detection, albeit at an increasing computational cost and with the necessity for high data quality. Here, we address concerns regarding robustness, automation, and experimental validation, optimizing both data acquisition and analysis. To make full use o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 55 publications
(117 reference statements)
0
31
0
Order By: Relevance
“…Fluorescence intensity traces associated with individual spots isolated from background were extracted and the number of photobleaching steps in each trace was determined (Fig. 8b, c ) 36 . Photobleaching step histograms show that majority (~71% of spots) of CD86-eGFP spots bleached in a single step consistent with a monomeric stoichiometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence intensity traces associated with individual spots isolated from background were extracted and the number of photobleaching steps in each trace was determined (Fig. 8b, c ) 36 . Photobleaching step histograms show that majority (~71% of spots) of CD86-eGFP spots bleached in a single step consistent with a monomeric stoichiometry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…If the labeling stoichiometry is not controllable, fluorescence calibration methods can help to strengthen the accuracy of the counting. Both synthetic nanostructures and intracellular proteins can be used as calibration systems to optimize the quantitative analysis, reducing miscounting errors (Hummert et al, 2021) and automatizing the analysis (Danial et al, 2022). However, stepwise photobleaching presents some intrinsic limitations.…”
Section: Stepwise Photobleachingmentioning
confidence: 99%
“…were included. Photobleaching steps were analyzed with use of quickPBSA package (Hummert et al, 2021).…”
Section: Liposomementioning
confidence: 99%
“…Previous work along these lines showed that the size distribution of the vesicles could be determined by correlating the fluorescence intensity of a lipid marker in single vesicles with DLS data (Hatzakis et al, 2009;Malle et al, 2021;Lohr et al, 2009;Olsson et al, 2015), and that tightness and lamellarity could be assessed by bleaching of the marker (Heider et al, 2011). Other studies used step-wise photobleaching assays to determine the copy number of fluorescent proteins per vesicle (Hummert et al, 2021). Here, we present a broadly applicable proteoliposome characterization assay at the single vesicle level that permits parallel analysis of multiple parameters (physical size, tightness, unilamellarity, membrane protein content and orientation) of individual proteoliposomes to provide a detailed picture of the reconstituted membrane system.…”
Section: Introductionmentioning
confidence: 99%